Coexistence of Gravitationally-bound and Radiation-driven C IV Emission Line Regions in Active Galactic Nuclei - Wang, Huiyuan; Wang, Tinggui; Zhou, Hongyan; Liu, Bo; Wang, Jianguo; Yuan, Weimin; Dong, Xiaobo (The Astrophysical journal, 2011)
There are mutually contradictory views in the literature of the kinematics and structure of high-ionization line (e.g., C IV) emitting regions in active galactic nuclei (AGNs). Two kinds of broad emission line region (BELR) models have been proposed, outflow and gravitationally-bound BELR, which are supported, respectively, by blueshift of the C IV line and reverberation mapping observations. To reconcile these two apparently different models, we present a detailed comparison study between the C IV and Mg II lines using a sample of AGNs selected from the Sloan Digital Sky Survey. We find that the kinematics of the C IV region is different from that of Mg II, which is thought to be controlled by gravity. A strong correlation is found between the blueshift and asymmetry of the C IV profile and the Eddington ratio. This provides strong observational support for the postulation that the outflow is driven by radiation pressure. In particular, we find robust evidence that the C IV line region is largely dominated by outflow at high Eddington ratios, while it is primarily gravitationally-bounded at low Eddington ratios. Our results indicate that these two emitting regions coexist in most AGNs. The emission strength from these two gases varies smoothly with Eddington ratio in opposite ways. This explanation naturally reconciles the apparently contradictory views proposed in previous studies. Finally, candidate models are discussed which can account for both the enhancement of outflow emission and suppression of normal BEL in AGNs with high Eddington ratios.